Analisis Sekuritisasi Uni Eropa terhadap Citizenship by Investment Program - Budi Sutrisno, Kharisma Fatiratri; Paramasatya, Satwika (Journal of International Relations, 2019)
Many countries in the world run Citizenship by Investment Programs (CIP) including European Union member countries, namely Bulgaria, Cyprus and Malta. CIP can open opportunities for financial crimes such as money laundering, corruption and tax fraud. In the European Union itself this raises more problems when the rules relating to granting citizenship in the European Union stating that every citizen of an EU member state is an EU citizen. Therefore, the European Union carries out a securitization policy towards CIP. This study aims to explain the securitization process that has been carried out through the concept of securitization from Copenhagen School and Amitav Acharya's modified model framework which consists of six elements namely issue area, securitizing actors, security concept, process, outcome and conditions affecting securitization. The result showed that the European Union's securitization process on the issue of Citizenship by Investment Program had run quite well but there were obstacles. These obstacles are the prerogative of the state in granting and losing citizenship also the existence of desecuritization actors